2020
DOI: 10.1111/jdi.13267
|View full text |Cite
|
Sign up to set email alerts
|

Polyneuropathy is inadequately treated despite increasing symptom intensity in individuals with and without diabetes (PROTECT follow‐up study)

Abstract: Aims/Introduction Despite its major clinical impact, distal symmetric polyneuropathy remains frequently undiagnosed and undertreated in clinical practice. We previously reported in the PROTECT Study that 70% of type 2 diabetes patients with distal symmetric polyneuropathy were unaware of having the latter condition. Materials and Methods In the present follow up after 2.5 ± 0.7 years, 122 and 85 participants with and without type 2 diabetes, respectively, completed questionnaires to obtain information about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
7
0
3
Order By: Relevance
“…Approximately 85% of LEA occur as a complication of diabetic foot ulcer (DFU), which is mainly caused by inadequate glucose control, peripheral artery disease, infection management, and polyneuropathy [7][8][9][10]. Evidence shows that a significant proportion of LEA in individuals with diabetes can be prevented by implementing effective multidisciplinary and multisectoral diabetes care programs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 85% of LEA occur as a complication of diabetic foot ulcer (DFU), which is mainly caused by inadequate glucose control, peripheral artery disease, infection management, and polyneuropathy [7][8][9][10]. Evidence shows that a significant proportion of LEA in individuals with diabetes can be prevented by implementing effective multidisciplinary and multisectoral diabetes care programs [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, in a longitudinal study over a 14‐y follow‐up period, the number of patients with polyneuropathy experiencing pain increased with time from 37% to 47% 18 . Moreover, Ziegler et al found that over a 2.5‐y follow‐up period about half the patients with polyneuropathy experience increasing sensory symptoms and pain 19 . In addition, in a longitudinal follow‐up study of patients with small fiber neuropathy, with an average follow‐up duration after diagnosis of 6.2 y, 86.1% noted pain at the initial visit, and 84.2% at the final visit 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Autonome Komplikationen wie die diabetische Gastroparese führen neben einer beeinträchtigten Nahrungsaufnahme zu verlängerten Wirklatenzen oral eingenommener Medikamente. Deafferenzierung und vaskuläre Fehlregulation begünstigen (postoperative) Wundheilungsstörungen bis hin zur Amputationsbedürftigkeit, und stumme Myokardinfarkte können zu spät erkannt und somit zu lange unbehandelt bleiben [7,8]. Umso wichtiger ist es, dass Diabetiker regelmäßig auf Neuropathiezeichen hin untersucht werden.…”
Section: Introductionunclassified
“…Leichtgradige Paresen, die nur in einer gezielten neurologischen Untersuchung auffallen, könnten bei vielen Betroffenen aber unerkannt sein. In allen Stadien sind neuropathische Schmerzen ein behandlungsbedürftiges Leitsymptom [8,18]. Diese sind auf eine Schädigung der C-und AδNervenfasern zurückzuführen, die nicht nur zusammen mit einer Large Fiber Polyneuropathie, sondern auch bei einer reinen Small Fiber Neuropathie auftreten kann [11,19].…”
Section: Introductionunclassified